Modes of immersion and stress induced by commercial (off-the-shelf) 3D games. (October 2014) - Bouchard, Stéphane; Bernier, François; Boivin, Éric; Guitard, Tanya; Laforest, Mylène; Dumoulin, Stéphanie; Robillard, Geneviève
Developing a stress-management training (SMT) system and protocol for soldiers can help them cope better with stress experienced in theatre operations. Using 3D horror games in virtual reality (VR) can present an attractive simulation method for soldiers. This study was conducted to find out whether it is possible to stress soldiers moderately using VR and which technology is more efficient to do so. A total of 47 soldiers returning from Afghanistan played two 3D first-person shooter (FPS)/horror games (Killing Floor and Left 4 Dead) on three different types of immersive technologies (a 22-inch stereoscopic monitor, a 73-inch stereoscopic TV and a CAVE™). As a control and reference comparison of induced stress, participants were exposed to the Trier Social Stress Test (TSST), a standardized stress-inducing procedure. Results were supporting of our work, devising an effective low-cost and high-buy-in approach to assist in teaching and practicing stress-management skills. Repeated measures analyses of variance (ANOVAs) revealed statistically significant increases in the soldiers' respiration rates and heart rates while playing the 3D games and during the TSSTs. No significant interactions were found. Increases in physiological arousal among the soldiers were significant when comparing the baseline to the immersion and to the TSST, but not when comparing both stressors. Immersion in 3D games is proposed as a practical and cost-effective option to create a context that allows practicing SMT.